PENGEMBANGAN ALAT PRODUKSI BIOETANOL LIMBAH KULIT UBI KAYU - Yuni Ernita; Prima Zola (Universitas Andalas, 2016)
The use of fossil fuels in Indonesia reached a high figure. On the other hand, the use of fossil fuels is not wise will result in global warming and climate change. Bioethanol is a source of renewable energy that can be (re-newable) with exhaust emissions of environmental friendly (eco-friendly). The raw material for bioethanol production is material sugary, starchy and fibrous. The purpose of research is to develop bioethanol production tools are appropriate and focus on the development of distillation equipment and conduct a performance test tool with leather waste materials which contain fiber cassava. Development of distillation equipment starting from the structural design is a design that reveals how the bioethanol distillation apparatus is composed of components that are built, the next is the functional design is a design that provides information about the function of components - tool components. The next stage is the process of making the main components and supporting components, followed by the assembly, finishing and testing equipment. The results of this research have been developed bioethanol distillation apparatus with the following specifications: Tank diameter 40 cm, height 60 cm tank, made of stainless steel with a thickness of 2 mm. Tank capacity of 40 liter.Dari trial results on skin distillation process results showed that the yield of cassava peel cassava ethanol produced was 10.3% at the distillation temperature and time 71ᵒC distillation for 5 hours, the ethanol distilled purity level is 63.4%, and 2.36 tool work capacity liters / hour.